Analysis of the Effect of Root Gap and Welding Voltage Variations on Weld Defects in GMAW Penetration - Muhammadanis Naufal Akif; Fica Aida Nadhifatul Aini (Jurnal Kendali Teknik dan Sains, 2026)
Welding is an essential process in the manufacturing industry, particularly in metal fabrication. Gas Metal Arc Welding (GMAW) is widely applied because of its efficiency and ability to produce high-quality welds. However, inappropriate welding parameters may increase the occurrence of weld defects, especially in the root penetration area of V-groove butt joints. This study aimed to evaluate the relationship between root gap and welding voltage variations and weld quality in the GMAW process, as well as to identify the best welding parameter combination among the tested conditions. This research employed a quantitative descriptive approach using an experimental design. S355J2C+N steel plates with V-groove butt joints were used as the test material. The welding parameters consisted of two root gap variations (2 mm and 3 mm) and three welding voltage levels (17 V, 18 V, and 19 V). Weld quality was evaluated using Non-Destructive Testing (NDT), including Visual Testing (VT) and Penetrant Testing (PT). The Fisher Exact Test indicated that neither root gap variation nor welding voltage variation had a significant relationship with the Visual Testing and Penetrant Testing results (p > 0.05). Based on the descriptive analysis, the combination of a 2 mm root gap and 18 V welding voltage produced the best weld quality among the tested specimens, with no discontinuities detected during Visual Testing and only one acceptable porosity indication identified during Penetrant Testing. These findings indicate that this parameter combination performed best under the experimental conditions of this study.